An Observational Study of Therapeutic Hypothermia and Factors Associated With Mortality in Late-Preterm and Term Neonates With Hypoxic-Ischemic Encephalopathy in a Middle-Income Country - Boo, Nem Yun; Neoh, Siew Hong; Chee, Seok Chiong; , for the Malaysian National Neonatal Registry (Frontiers in Pediatrics, 2022)
Objectives To investigate the types of therapeutic hypothermia (TH) used and risk factors associated with mortality in late-preterm and term neonates (LPTN, gestation of ≥35 weeks) with hypoxic-ischemic encephalopathy (HIE) in a middle-income country. Design This was an observational retrospective cohort study. Setting A total of 44 neonatal intensive care units (NICUs) in the Malaysian National Neonatal Registry participated in the study. Patients All LPTN without major malformations and diagnosed to have HIE were included. Main Outcome Measures Number of in-hospital mortality, and types of TH used [no TH, TH using commercially available servo-controlled devices (SCDs), passive TH by exposing neonates to NICU’s air-conditioned ambient temperature with/without the use of cooled gel packs (P±CGPs)]. Results Of a total of 2,761 HIE neonates, 66.3% received TH. All NICUs provided TH; 55.4% NICUs had SCDs, which was administered to 43.6% (248/569) of severe, 51.6% (636/1,232) of moderate, and 18.6% (179/960) of mild HIE neonates. P±CGPs was used on 26.9% of severe, 33.4% of moderate, and 21.1% of mild HIE neonates. There were 338 deaths. Multiple logistic regression analysis showed that 5-min Apgar scores <5 (aOR: 1.436; 95% CI: 1.019, 2.023), Cesarean section (aOR: 2.335; 95% CI: 1.700, 3.207), receiving no TH (aOR: 4.749; 95% CI: 3.201, 7.045), TH using P±CGPs (aOR: 1.553; 95% CI: 1.031, 2.338), NICUs admitted <50 HIE cases (aOR: 1.898; 95% CI: 1.225, 2.940), NICUs admitted 50-<100 HIE cases (aOR: 1.552; 95% CI: 1.065, 2.260), moderate HIE (aOR: 2.823; 95% CI: 1.495, 5.333), severe HIE (aOR: 34.925, 95% CI: 18.478, 66.012), Thompson scores of 7–13 (aOR: 1.776; 95% CI: 1.023,3.082), Thompson scores of ≥14 (aOR: 3.641; 95% CI: 2.000, 6.629), pneumothorax (aOR: 3.435; 95% CI: 1.996, 5.914), and foreigners (aOR: 1.646; 95% CI: 1.006, 2.692) were significant risk factors associated with mortality. Conclusion Both SCD and P±CGP were used for TH. Moderate/severe HIE and receiving passive/no TH were among the risk factors associated with mortality.